The enhancement of spaces in between buildings as urban recreation development / Zalina Haji Samadi and Mohd Nasuruddin Hasbullah - Samadi (Haji), Zalina; Hasbullah, Mohd Nasuruddin (2008)
Whenever developers or building owners develop a specific parcel of land, the focus of the development is mainly within their boundaries. The space left in between buildings is just enough to allow fire engine to access. Besides fire requirement, space in between buildings is to fulfil the minimum distance requirement by the local authority. As a consequence of that; the space in between buildings is only a space without proper intention. It is a leftover space without designated function. Examples of such spaces area are the rear, the side of buildings and under the flyovers or bridges. Even though most of local controller have their own expert advisory-committee, it doesn’t mean the whole city development is well taken-care. Without any awareness on the significance of such spaces; the space will be occupied by a group of the urban community for their own personalisation space. To some extends they used those spaces for negative activities. If this continuous; the city safety, security and surveillance will be threatened. Therefore, in line with the acceleration of urban transition for mega-city in the East Coast Economic Region; it is a call for multi disciplinarians to focus on the future of those spaces in the city.